Sex Bias in Asthma Prevalence and Pathogenesis - Shah, Ruchi; Newcomb, Dawn C. (Frontiers in Immunology, 2018)
Sex-related differences in asthma prevalence are well-established and change through the reproductive phases of life. As children, boys have increased prevalence of asthma compared to girls. However, as adults, women have increased prevalence of asthma compared to men. Many factors, including genetics, environment, immunological responses, and sex hormones, affect the gender disparity associated with the development and control of asthma and other allergic diseases. Fluctuations of hormones during puberty, menstruation, pregnancy, and menopause, alter asthma symptoms and severity. The mechanisms driving these processes remain unclear and additional clinical, epidemiological, and animal studies are warranted to decipher the role of sex hormones and X chromosome dosage on asthma prevalence and severity. In this article, we review clinical and epidemiological studies that have examined the gender disparity and effect of sex hormones on asthma pathogenesis.